KEDUDUKAN PERATURAN PEMERINTAH PENGGANTI UNDANG-UNDANG DALAM SISTEM PERATURAN PERUNDANG-UNDANGAN DI INDONESIA. - Almanar, Husni A. Jalil, Nur Rasyid. (Jurnal Ilmu Hukum, 2015)
Abstract: Article 22 (1) of the Constitution of Republic of Indonesia of 1945 reads that in emergency time the President entitles to issue a government regulation to substitutes act. The problems are the conditions necessary of making a government regulation to substitute act, and toneed to know the considerations of the Parliament of acceptance or refusal of this government regulation. The research purposes are to analyze the necessery conditions regarding the conditions to marlee this regulation and Parlimentary conciderations to accept or refuse it. The research method applies Juridical-normative concepts by approaching legal drafting technique, document analyzeing by contents analysis technique. Data gathering by analyzing the relevant theoris, legal rule making, opinion of the experts, reading, books. journal and news paper. The research result shows that government regulation to substitute act. as a part of hierarchy of legal rule of Republic of Indonesia and it is equal act.that is needed in emergency time. The conditions for emergency basis of making this government regulation to substitute act, is essential to be stipulated in legal rule hierarchy. The legal basis of the Parliament to accept or refuse government regulation to substitutes act. is the Article 22 of the Constitution of Republic of Indonesia of 1945 and Act No. 12 of 2011 on the making of legal rule (legal drafting), The government regulation to substitutes act must have approval from the Parliament, government regulation to substitutes act is diclared to be approved. It is recommended that the Government and Parliament to emergency situation and to make use Presidential Advisor Board so that issuance of government regulation to subtitute act the meets the principles of democracy rule of law and public accountability. Contitusional Court is not authorized to review this government regulation to subtitute act. Keywords : Government Regulation To Substitute Act, and Legal Rule system. Abstrak: Pasal 22 ayat (1) Undang-Undang Dasar 1945 menyebutkan bahwa “ dalam hal ihwal kegentingan yang memaksa”, Presiden berhak menerbitkan peraturan pemerintah sebagai pengganti undang-undang”, yang menjadi masalah adalah tentang syarat mengenai “kegentingan yang memaksa” sebagai dasar pertimbangan penerbitan Perpu. Dan untuk mengetahui pertimbangan hukum DPR dalam menerima dan menolak. Perpu. Tujuan Penelitian ini adalah untuk menganalisa syarat yang harus ada dalam penerbitan Perpu, dan pertimbangan DPR untuk menerima dan menolak Perpu. Metode penelitian yang digunakan adalah konsep penelitian yuridis normatif dengan pendekatan teknik pembentukan perundang-undangan. Data diperoleh dengan menelaah teori-teori, Peraturan Perundang-undangan, pendapat para pakar, buku, jurnal, majalah dan surat khabar yang relevan. Hasil penelitian menunjukkan Perpu merupakan bagian dari hirarki dan setara dengan undang-undang. Perpu perlu ada dalam situasi darurat. Adapun syarat “Kegentingan memaksa” sebagai dasar bagi pembentukan Perpu perlu ditetapkan dalam peraturan perundang-undangan. Dasar hukum DPR menerima dan menolak Perpu, adalah Pasal 22 Undang-Undang Dasar 1945 dan Undang-Undang Nomor 12 Tahun 2011 tentang pembentukan peraturan perundang-undangan, bahwa Perpu harus mendapatkan persetujuan dari DPR. Perpu dinyatakan diterima atau ditolak. Disarankan untuk Pemerintah dan DPR perlu melakukan revisi Undang-Undang Nomor 12 Tahun 2011 tentang Pembentukan Peraturan Perundang-undangan khususnya yang mengatur persyaratan “Kegentingan yang Memaksa”, serta memfungsikan Wantimpres dengan tugas khusus, sehingga penerbitan Perpu memenuhi prinsip demokrasi, negara hukum dan akuntabilitas publik. Mahkamah Konstitusi (MK) tidak berwenang melakukan pengujian Perpu. Kata Kunci : Perpu dan Sistem perundang-undangan.